2021
DOI: 10.1002/anie.202017042
|View full text |Cite
|
Sign up to set email alerts
|

Selective Crystallization of Rare‐Earth Ions into Cationic Metal‐Organic Frameworks for Rare‐Earth Separation

Abstract: For rare-earth separation, selective crystallization into metal-organic frameworks (MOFs) offers new opportunities. Especially important is the development of MOF platforms with high selectivity toward target ions. Here we report a MOF platform (CPM-66) with low-coordinationnumber environment for rare-earth ions. This platform is highly responsive to the size variation of rare-earth ions and shows exceptional ion-size selectivity during crystallization. CPM-66 family are based on M 3 O trimers (M = 6-coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 45 publications
(8 reference statements)
0
37
0
Order By: Relevance
“…47 In 2016, Sa ´nchez et al 48 reported similar results for NOTT-401, where the capacity improved from 1.2 wt% (under dry conditions) to 3.9 wt% under 5% RH at 30 1C. 49 Colour code: C, gray; O, red; Sc, purple; S, yellow; N, green; H, white.…”
Section: Sc(ch 3 Coo) 3 and [Sc(clch 2 Coo) 3 ]mentioning
confidence: 82%
See 2 more Smart Citations
“…47 In 2016, Sa ´nchez et al 48 reported similar results for NOTT-401, where the capacity improved from 1.2 wt% (under dry conditions) to 3.9 wt% under 5% RH at 30 1C. 49 Colour code: C, gray; O, red; Sc, purple; S, yellow; N, green; H, white.…”
Section: Sc(ch 3 Coo) 3 and [Sc(clch 2 Coo) 3 ]mentioning
confidence: 82%
“…One of the two kinds of pores identified in the MOF is filled with pendant urea solvents and nitrate ions. The compound exhibits a BET area of 172.7 m 2 g À1 and high thermal stability up to 300 1C 49. {[Sc(l-pmdc)(l-ox) 0.5 (H 2 O) 2 ]Á3H 2 O} n , {[Sc(l-pmdc)(l-OH) (H 2 O)]ÁH 2 O} n , {(NH 4 )[Sc(l-ox) 2 ]Á2H 2 O} n , {(tma) 2 [ScK(l-form) 6 ]} n , and [Sc 2 (pmdc)(OH) 3 Cl]ÁDMFÁ2H 2 O. Cepeda et al (2015) 50 studied the factors governing the hydro-and solvothermal reactions of ScCl 3 with pyrimidine-4,6-dicarboxylic acid (H 2 pmdc) (Scheme 1), which afforded {[Sc(m-pmdc)(m-ox) 0.5 (H 2 O) 2 ]Á3H 2 O} n (10), {[Sc(m-pmdc) (m-OH)(H 2 O)]ÁH 2 O} n (11), {(NH 4 )[Sc(m-ox) 2 ]Á2H 2 O} n (12), {(tma) 2 [ScK(mform) 6 ]} n (13), and [Sc 2 (pmdc)(OH) 3 Cl]ÁDMFÁ2H 2 O (14) (ox = oxalate, tma = tetramethylammonium, form = formate) (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their toxicity and reactivity, expensive safety measures are required to handle, store, and transport these gases safely, thereby placing their usage in synthetic chemistry under strict regulations [7] . Herein, we probed metal‐organic frameworks (MOFs), [8–33] specifically their reversible gas adsorption and catalytic activity, to carry out chemical reactions in organic solvents. Thus, we explored the dual role of MOFs as a catalyst and carrier of reagents on the example of reactive gases.…”
Section: Introductionmentioning
confidence: 99%
“…Figure2. Structures of CPM-66 [17]. a) the formation of trimer building blocks in CPM-66A and CPM-66B; b) acs topology of CPM-66; c) the framework of CPM-66B viewed along c direction; d) rare-earth ions with their corresponding ionic radii (unit: pm) at coordination number of 6 (In 3+ is also included).…”
mentioning
confidence: 99%